Cover Feature: Persulfate Reaction in a Hair‐Bleaching Formula: Unveiling the Unconventional Reactivity of 1, 13‐Diamino‐4, 7, 10‐Trioxatridecane (ChemistryOpen 5/2018). Issue 5 (16th April 2018) - Gargano, Emanuele M.; Mangiatordi, Giuseppe F.; Weber, Ingo; Goebel, Carsten; Alberga, Domenico; Nicolotti, Orazio; Ruess, Wolfgang; Wierlacher, Stefan
Abstract : The Cover Feature shows a persulfate reaction occurring under the conditions of a cosmetic hair bleaching procedure, applied worldwide to lighten hair. 1, 13‐diamino‐4, 7, 10‐trioxatridecane is an ingredient marketed to hair salons and consumers for a so‐called "plex" service. In a model bleach it partially reacts and forms an unexpected azanyl ester whose occurrence is considered relevant for the toxicological assessment. More information can be found in the Communication by E. M. Gargano et al. onpage 319 in Issue 5, 2018 (DOI:10.1002/open.201800013 ).